Konstruksi Sosial Kepatuhan Pajak di Indonesia: Telaah Literatur Antropologi Ekonomi - Eko Budi Prasetyo; Anita Anita; Rosiana Ramadhon; Neneng Yanti Andriani; Partiwi Partiwi; Eka Ningsih Puji Rahayu (Alpatih Harapan Semesta, 2026)
Tax compliance is a crucial factor in sustaining state revenue; however, studies on compliance behavior in Indonesia remain dominated by economic and tax administration perspectives, leaving socio-cultural aspects under-examined. This study aims to analyze the social construction of tax compliance in Indonesia through the lens of economic anthropology by reviewing relevant scholarly literature. A qualitative approach utilizing a literature review design was employed. Secondary data were gathered from accredited national journals, reputable international journals, scholarly books, conference proceedings, and policy documents concerning tax compliance, economic anthropology, and social construction. Data were analyzed using qualitative content analysis, involving stages of identification, coding, categorization, synthesis, and thematic interpretation. The findings reveal that tax compliance is a social reality shaped by the interplay of cultural values, social norms, tax morality, civic identity, and the level of public trust in the state. Collective values ​​within society shape perceptions of tax obligations as a form of social responsibility, while institutional legitimacy and the quality of governance influence the level of voluntary taxpayer compliance. Furthermore, local culture and social capital reinforce the internalization of compliance values ​​when supported by a transparent, fair, and accountable tax system.